Records of bentfin devil ray, Mobula thurstoni, in a marine protected area in Brazilian Equatorial Atlantic: implications for the species’ distribution and local conservation strategies - Bucair, Nayara (2022)
The bentfin devil ray (Mobula thurstoni) is a migratory elasmobranch species with a wide distribution range. Despite the recent increase in mobulid research, critical habitats and home ranges are still being identified for these threatened species. In the present study, photo and video records opportunistically gathered by SCUBA diving effort were used to identify individuals and habitat usage by M. thurstoni in a marine protected area in the western equatorial Atlantic Ocean, Fernando de Noronha Archipelago (FNA). The bentfin devil ray was identified in five distinct records, in different years and sites around the archipelago. All the males showed developed claspers, suggesting mature individuals using the area. The UNESCO heritage site of FNA is considered an area of high biological importance, containing essential habitats for several species of fish, turtles and marine mammals. However, habitat usage by devil ray species is poorly reported in the region; therefore, the present study presents the first report of M. thurstoni at FNA, which adds the fifth mobulid ray species recorded in the region. Additionally, these results correspond to the second record of living specimens of M. thurstoni in Brazilian jurisdictional waters, highlighting new information on the species’ distribution and the home range of mobulids in Brazil.